Yellow light-emitting electrochemical cells utilizing iridium(III) phenanthroimidazole complexes. (2nd September 2017) - Jo, Suin; Choe, Y. S.
ABSTRACT: The utilization of cationic iridium complexes in light-emitting electrochemical cells (LECs) have drawn remarkable attention over other metal complexes, because of their large ligand-field splitting energies (LFSEs). Herein, we report two new cationic iridium complexes using phenanthroimidazole derivatives as ancillary ligand, namely, [Ir(ppy)2 (ptpphim)]PF6 (complex 1) and [Ir(meppy)2 (ptpphim)]PF6 (complex 2). The photoluminescence (PL) emission spectra in acetonitrile solution show yellow emission for complex 1 (540 nm) and complex 2 (561 nm). LECs were fabricated and emitted yellow light with the CIE coordinates of (0.46, 0.52) and (0.49, 0.50) for complex 1 and 2, respectively. Complex 1 shows the higher current efficiency of 0.56 cd A −1 than complex 1 (0.26 cd A −1 ) due to the lower current current density of the former. The use of phenanthroimidazole with a bulky tetraphenyl methane group reduce the intermolecular interactions between the iridium complexes, thereby enhancing device performances.